Performance measurement system and managerial performance in response to public sector change: the moderating effects of perceived readiness for change / Nazirah Aziz - Aziz, Nazirah (Institute of Graduate Studies, UiTM, 2018)
The Government Transformation Program (GTP) has been established in 2009 in an effort to improve performance of public sector organizations, which include improvement in managerial performance. This study views the GTP as the change program initiated by the government to improve performance and service delivery towards the public at large. The present study asserts the significance of inculcating managers’ Perceived Readiness for Change (PRC) in the study of Performance Measurement System (PMS) towards improving public sector performance. So far, however, there has been little discussion on the role of PRC in enhancing the relationship between PMS and managerial performance. The present study explores the pattern (based on the response pattern of respondents on the Person-Item Distribution Map of Rasch Analysis) of managerial performance, PMS and PRC after the implementation of GTP. The present study also investigates the relationship between PMS and PRC on the managerial performance. This study also examines the role of PRC in moderating the relationship between PMS and managerial performance. A mix method approach using the survey with follow-up interviews was employed to achieve the research objectives. The survey for this study was conducted over five ministries directly working with the National Key Results Areas (NKRAs), as the NKRAs are the main indicators of GTP. Rasch Measurement Model and Winsteps@3.72.3, SPSS version 21 and PROCESS analysis were used to analyze the data…